Rising trends of caesarean section in modern obstetrics: analysis by Robson classification - Rajakumar, Shery Angel; Myneni, Sindhura; M., Kamala Roshini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Rising caesarean section (CS) rates are a major public health concern worldwide. The main objective of our study was to analyse the CS rates according to Robson ten group classification system (TGCS). Methods: This was a retrospective study conducted in the department of obstetrics and gynaecology at Chettinad hospital and research institute, during a period of 5 years from May 2015 to April 2020. All the women who delivered by CS were included in the study. The data regarding parity, gestational age, onset of labour, number of foetuses and presentation was collected and classified according to Robson TGCS and analysed. Results: A total of 4199 women delivered during the study period. Out of 4199 women 2149 (51.18%) underwent CS. All the women who underwent caesarean section were classified according to Robson TGCS. Group 5 contributed the most (40.81%). Group 2 had the second highest contribution of 33.36%. Group 1 had 6.24%, group 3 and 4 contributed for 1.16% and 4.65% respectively. Group 6 and 7 had 2.84% and 1.68% respectively. Group 8 had 2.28%, group 9 had 0.23% and group 10 constituted 6.75%. Conclusion: As contribution of repeat CS is high among the overall CS rate it is important to reduce the primary CS rates. More analytical studies need to be done based on Robson TGCS to evaluate the indication of CS within each group.